Drawing a line: Comparing the estimation of top incomes between tax data and household survey data - Nishant Yonzan; Branko Milanović; Salvatore Morelli; Janet C. Gornick (Luxembourg Income Study (LIS), 2020)
The paper uses the flexibility of household survey data to align their income categories and recipient units with the income categories and units found in data produced by tax authorities. Our analyses, based on a standardized definition of fiscal income, allow us to locate, for top-income groups, the sources of discrepancy. We find, using the cases of the United States, Germany, and France, that the results from survey-based and tax data correspond extremely well (in terms of total income, mean income, composition of income, and income shares) above the 90th percentile and up to the top 1 percent of the distribution. Information about income composition, available in the US, allows us to investigate the determinants of this gap in the US. About three-fourths of the tax/survey gap is due to differences in non-labor incomes, especially self-employment (business) income. The gap itself may be due to tax-induced re-classification of income from corporate to personal or/and to lower ability of surveys to capture top 1 percent incomes.
Keywords: D31; 330; Income; inequality; survey data; tax data